(untitled) (Journal of Philosophy Culture and Political Science, 2015)
The article analyzes the political point of view with Zhaһanshy Dosmukhamedov role in the conduct of the Congress of Kazakhs Oralskoy area, his public activities, as well as political views based on historical data. J. Dosmukhamedov known as the leader of Western Alashorda, but with political point of view political activity as J. Dosmukhamedov chairman of the Congress of Kazakhs Oral area is still not widely appreciated, its role in the congress and organizations insufficiently investigated. The article discusses his work, the idea of preserving the national identity, the future structure of the state, the importance of creating an autonomous democratic republic within the federation.